Ambulatory monitoring of pulmonary artery pressure. A preliminary clinical evaluation. Issue 1 (January 1983) - Nathan, A W; Perry, S G; Cochrane, T; Banim, S O; Spurrell, R A; Camm, A J
Abstract : Traditional measurement and recording methods are inadequate for continuous monitoring of ambulatory pulmonary artery pressure. Therefore a new miniaturised solid state system has been developed and assessed. A manometer tipped catheter, inserted via a subclavian or cephalic vein, was used together with an isolated amplifier and peak detectors to determine systolic and diastolic pressures. Pressures were averaged over 30 seconds and stored in digital memory. After a 24 hour recording period data were rapidly transferred to a microcomputer for numerical or graphical display. Thirteen patients had continuous ambulatory monitoring performed for between 24 and 96 hours, in seven to evaluate symptoms of dyspnoea in subjects with valvular or coronary disease (group 1), and in six to achieve optimal oral treatment for left heart failure (group 2). The catheter was calibrated before insertion and was rechecked after removal. There was less than 1% zero level drift and similar gain stability. Systolic pressures ranged from 10 to 97 (mean 39.5) mmHg, and diastolic from 1 to 46 (mean 15.3) mmHg. Four patients in group 1 had symptoms of dyspnoea associated with normal pressures, while three had raised pressures. Four of the six patients monitored in group 2 had major alterations in their treatment based on data obtained during monitoring. There were no complications. This system, which allows safe, reliable, and prolonged recording of ambulatory pulmonary artery pressure, represents a considerable advance in the ability to assess the cause of dyspnoea and to manage left heart failure.